Landslide-water Interaction for Partially Submerged Landslide - Kafle, Jeevan; Tuladhar, Bhadra Man (Journal of Nepal Mathematical Society, 2018)
Tsunamis are long water waves triggered by impulsive geologic events. Tsunamis generated by landslides may be classified based on the initial position of the landslide as subaerial, partially submerged or submarine landslide generated tsunamis depending on the initial position of the landslide relative to the water depth. Here we present and discuss a simulation related to a partially submerged landslide in a quiescent reservoir by using the general two-phase mass flow model (Pudasaini, 2012) to observe the explicit evolution and propagation of surface tsunami waves, and solid waves as submarine mass movement. Tsunami waves are reflected as they impact the right coast and the lateral walls of the reservoir. The study of wave propagation, reflection and interaction as well as the submarine mass movement enhance our understanding on the tsunami-related phenomena and the turbidity current in water bodies and coastal areas.